Peran NGO (Non-Governmental Organization) dalam Pengimplementasian Urban Farming Sebagai Strategi Adaptasi Di Kecamatan Koto Tangah, Kota Padang - Rinawati Rinawati; Tarma Sartima; Annisa Fitri; Nika Saputra (UNES Law Review, 2023)
Urban farming has the potential to increase family knowledge in disaster preparedness. Through urban farming practices, families can gain relevant knowledge and skills to better deal with disasters. In the context of coastal communities in Koto Tangah subdistrict in Padang City which are vulnerable to disasters such as earthquakes and floods, urban farming can be an effective strategy in preparing families to face emergency situations. Urban farming has become a vital strategy in dealing with climate change and increasing food security in various urban communities. In this context, Non-Governmental Organizations (NGOs) play a central role in implementing and expanding urban farming practices. This research focuses on the role of NGOs in implementing urban farming in Koto Tangah District, Padang City. NGOs act as policy advocates, mobilizing support and driving change in urban agricultural management. Training organized by NGOs increases community knowledge and skills related to urban farming, creating positive behavioral changes. Effective outreach increases understanding of the sustainability and benefits of urban farming. In seeding and planting activities, NGOs provide significant support through the distribution of planting media, seeds and fertilizer. This results in increased capacity, confidence and savings in family expenses. Overall, the role of NGOs in urban farming in Koto Tangah District not only creates a practical transformation in food production, but also has a positive impact on awareness, disaster preparedness and environmental sustainability. This research provides a holistic picture of how NGO interventions can be a catalyst for change in urban communities through the implementation of urban farming.